Clinical and epidemiological characteristics and associated factors of hair graying: a population-based, cross-sectional study in Turkey, - Ersoy Acer; Didem Arslantaş; Gülsüm Öztürk Emiral; Alaattin Ünsal; Burcu Işıktekin Atalay; Saniye Göktaş (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background Hair graying is common in humans; but there is scarce data about its epidemiology. Objective This study aimed to evaluate the clinical and epidemiological characteristics and associated factors of hair graying. Methods A total of 1541 volunteers between 15 and 65 years old were included in this population-based, cross-sectional study. A questionnaire on characteristics and associated factors of hair graying was filled in by face-to-face interview method. Results One thousand sixty three participants (69.0%) had hair graying. The mean onset age of hair graying was 32.9 ± 9.8 years. It was 31.7 ± 9.5 years in females, whereas 33.7 ± 10.0 years in males (p = 0.001). The most common involved area of hair graying at the onset and at the time of the interview was temporal region. When it was evaluated by gender, it was temporal in males whereas parietal in females. Hair graying was more severe in males than in females and in late-onset hair graying than early-onset hair graying (respectively, p = 0.000, p < 0.001). The most common involved area at the onset and at the present was temporal in severe hair graying; whereas parietal in mild hair graying. In logistic regression analysis, age, educational status, presence of hair loss, skin type, family history of early-onset hair graying and anxiety were independently related to hair graying (p < 0.05). Study limitations The study was performed in only Turkish individuals. The recall biases were another limitations. Conclusion Male gender, late-onset and temporal-onset of hair graying may be considered to be poor prognostic factors for hair graying. There is need for further epidemiological studies in people with different ethnic origin to illuminate the clinical and epidemiological characteristics and associated factors of hair graying.